Políticas públicas na formação em bacharelado em Educação Física da ESEF-UFPel - Silva, Vítor Tavares da (2020)
The aim of this study was to better understand the Bachelor’s degree in Physical Education at Escola Superior de Educação Física of the Universidade Federal de Pelotas (ESEF-UFPel) regarding the articulation of the theme public policies. The study aimed at identifying how the course articulates this theme in curricular subjects and professional internships and problematizing the training of students regarding public policies. This study fits the mold of the qualitative paradigm, using a focus group to collect data with the participation of students from the bachelor's degree course in 2019. Three meetings were organized with 12 undergraduates, developing the discussion about relevant topics to the students. The research corpus was enriched by using a field diary which was explored in its descriptive and reflective dimensions. Data analysis was carried out according to Discursive Textual Analysis assumptions. Thus, the results highlighted that the limitation and development of the theme public policy rely on the conditions of poor and isolated experiences. According to the students, it depends on the interest and availability of the teacher. All of this takes place in the context of a fragmented course hosting only subjects related to human and social sciences, the space for the debate of social issues, along with the passivity of most of the students in curricular practices. In addition, the Bachelor’s degree course seems strongly resistant to initiatives linked to internships in public institutions, as the systema tization of professional internships occurs, in large part, around private institutions, such as fitness centers. At the same time, the scenario of public policies that are sensitive to PE is increasingly eroded by the crisis of representativeness with the political class, as well as by the worsening of economic policies in Brazil in the last decades, due to the lack of investments in the public sector. Therefore, it was concluded that ESEF-UFPel favors, as well as the national higher education scenario as a whole, the training profile linked to the demands of the private sector, acting as a public education institution which does not articulate professional training in the Bachelor’s degree in PE in a structured way along with the public sector.